Kebijakan Merdeka Belajar dan Implikasinya Terhadap Desain Model Perkuliahan PAI di Perguruan Tinggi Islam - Ibadin, Hasan; Musthofa, Musthofa; Arifi, Ahmad (Nusantara: Jurnal Pendidikan Indonesia, 2023)
The progress of science and technology causes cultural, social, political, and economic changes as well as the world of work. There are jobs that are missing or that are popping up according to today's profession. For example, the PAI teaching profession does not only know educational theory but needs to master various other disciplines. Because of this, it is necessary to increase the development of human resources for superior Islamic education graduates who are ready to go according to the needs of society, industry, and experience in the world of work. The purpose of this research is to find out the role of Islamic Religious Higher Education in improving and building superior human resources in the PAI Study Program after the publication of the independent learning-free campus curriculum. This study uses a qualitative method with a literature study approach. The results of this study indicate that there is support for Islamic tertiary institutions to apply this policy, namely by making a design model for the implementation of the Merdeka curriculum program that is applied to the PAI study program. The design described is by providing three semester learning rights with three models in the implementation of lectures (block, non-block, and regular models). This program opens wide opportunities for PAI students to enrich and improve their insights and competencies in the real world according to their passion and aspirations.